2021
DOI: 10.1002/mp.15109
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of scintillator–reflector optical interfaces for the LUT Davis model

Abstract: Purpose Designing and optimizing scintillator‐based gamma detector using Monte Carlo simulation is of great importance in nuclear medicine and high energy physics. In scintillation detectors, understanding the light transport in the scintillator and the light collection by the photodetector plays a crucial role in achieving high performance. Thus, accurately modeling them is critical. Methods In previous works, we developed a model to compute crystal reflectance from the crystal 3D surface measurement and stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The optical photons produced by scintillation and Cerenkov emission from energetic electrons were simultaneously generated and tracked using the Livermore Model [28]. The transport of optical photons was conducted using the LUT Davis model [29][30][31][32][33] with polished surfaces LUTs wrapped in Teflon, except the face in contact with the photodetector, which was modeled coupled to optical grease (index of refraction 1.5) for all simulations.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…The optical photons produced by scintillation and Cerenkov emission from energetic electrons were simultaneously generated and tracked using the Livermore Model [28]. The transport of optical photons was conducted using the LUT Davis model [29][30][31][32][33] with polished surfaces LUTs wrapped in Teflon, except the face in contact with the photodetector, which was modeled coupled to optical grease (index of refraction 1.5) for all simulations.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Previous work has shown that although QE increases as the detector element thickness increases, it does not always lead to a higher light output 28 . Light output depends on a variety of optical properties that should be carefully chosen in order to gain optimal performance 32,46 . For the parameters used in the present study, the increase in CsI:Tl crystal thickness from 10 to 60 mm did not increase the number of optical photons exiting from a typical element, although the total number of optical photons generated in that element increased (Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…28 Light output depends on a variety of optical properties that should be carefully chosen in order to gain optimal performance. 32,46 For the parameters used in the present study, the increase in CsI:Tl crystal thickness from 10 to 60 mm did not increase the number of optical photons exiting from a typical element, although the total number of optical photons generated in that element increased (Figure 3). The light loss occurs due to longer pathways that the majority of optical photons have to traverse, and the corresponding increase in the number of incidences on the detector element wall in thicker elements, which causes a reduction in light collection efficiency and an increase in the optical Swank noise.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations